Oxygen carrier and reactor development for chemical looping processes and enhanced CO2 recovery - Haider, Syed Kumail (Cranfield University, 2016)
This thesis’s main focus is a CO2 capture technology known as chemical looping combustion (CLC). The technology is a novel form of combustion and fuel processing that can be applied to gas, solid and liquid fuels. By using two interconnected fluidised-bed reactors, with a bed material capable of transferring oxygen from air to the fuel, a stream of almost pure CO2 can be produced. This stream is undiluted with nitrogen and is produced without any direct process efficiency loss from the overall combustion process. The heart of the process is the oxygen carrier bed material, which transfers oxygen from an air to fuel reactor for the conversion of the fuel. Oxygen carrier materials and their production should be of low relative cost for use in large-scale systems. The first part of this research centres on development and investigative studies conducted to assess the use of low-cost materials as oxygen carriers and as supports. Mixed-oxide oxygen carriers of modified manganese ore and iron ore were produced by impregnation. While copper (II) oxide supported on alumina cement and CaO have been produced by pelletisation. These oxygen carriers were investigated for their ability to convert gaseous fuels in a lab-scale fluidised bed, and characterised for their mechanical and chemical suitability in the CLC process. The modified ores and pelletised copper-based oxygen carriers’ mechanical properties were enhanced by their production methods and in the case of the modified iron ore, significant oxygen uncoupling was observed. The copper-based oxygen carriers particularly those containing alumina cement showed high conversion rates of gaseous fuels and improved mechanical stability. The second part of this research thesis focuses on the design philosophy, commissioning and operation of a dual-fast bed chemical looping pilot reactor. Based on the operational experience, recommendations for modifications to the CLC system are discussed. In support, a parallel hydrodynamic investigation has been conducted to validate control and operational strategies for the newlydesigned reactor system. It was determined that the two fast bed risers share similar density and pressure profiles. Stable global circulation rate is flexible and could be maintained despite being pneumatically controlled. Reactor-reactor leakage via the loop-seals is sensitive to loop seal bed-height, and inlet fluid velocity but can be maintained as such to ensure no leakage is encountered.
Keywords: Climate change; Carbon capture; Circulating fluidised bed; Metal oxide; Ore; Oxygen uncoupling (CLOU)